Risk factors for gastrointestinal bleeding in children with Henoch-Schönlein purpura - Dequan Su; Mi Yang; Xiaoqin Wang; Guangbo Li; Shaoxian Hong (Frontiers in Pediatrics)
ObjectiveTo analyze the risk factors associated with gastrointestinal bleeding in pediatric patients with Henoch-Schönlein purpura (HSP), with the goal of enhancing early diagnosis and treatment, preventing complications, and improving patient outcomes.MethodsThe study involved 23 pediatric patients with HSP who experienced gastrointestinal bleeding, forming the study group. They were admitted to our hospital from June 2023 to June 2024. For comparison, a control group composed of 44 children with HSP but without gastrointestinal bleeding, admitted during the same timeframe, was established. Data on clinical characteristics, laboratory results, and imaging findings were collected. Both univariate and multivariate analyses were conducted to identify potential risk factors.ResultsA total of 67 children with HSP were divided into two groups: those with gastrointestinal bleeding (23 cases) and those without (44 cases). The occurrence of abdominal pain and incidence of intestinal wall thickening detected by gastrointestinal ultrasonography were significantly higher in the group with gastrointestinal bleeding compared to the group without bleeding (P < 0.05). Univariate analysis revealed significant differences in eight laboratory parameters (WBC, NE, NLR, PCT, CRP, D-dimer, Fib, TT), all statistically significant (P < 0.05). Multivariate analysis identified three independent risk factors for gastrointestinal bleeding in children with HSP: abdominal pain (OR = 2.334, 95% CI: 0.458–11.886, P = 0.010), a PCT level above 0.12 ng/ml (OR = 10.010, 95% CI: 1.208–82.929, P = 0.033), and a D-dimer level exceeding 1.87 mg/L (OR = 3.407, 95% CI: 1.022–17.473, P < 0.001).ConclusionThe findings confirmed that abdominal pain, elevated PCT levels, and increased D-dimer are significant independent risk factors for gastrointestinal bleeding in pediatric patients with Henoch-Schönlein purpura. Clinicians should monitor these indicators attentively to enhance patient management and outcomes.